A survey of syphilis knowledge among medical providers and students in Rhode Island. (February 2020) - Bonnewell, John; Magaziner, Sarah; Fava, Joseph L; Montgomery, Madeline C; Almonte, Alexi; Carey, Michael; Chan, Philip A
Background: In the United States, syphilis cases have increased dramatically over the last decade. Recognition and timely diagnosis by medical providers are essential to treating syphilis and preventing further transmission. Methods: From 2016 to 2017, a cross-sectional survey was performed among medical students, residents, fellows, and attending physicians in Rhode Island. Topics included demographics, level of medical training, experience diagnosing and treating syphilis, and familiarity with the reverse testing algorithm. Participants were asked 25 true/false questions to assess basic knowledge of syphilis, which covered five domains: epidemiology, transmission, clinical signs and symptoms, diagnosis, and treatment. Univariate and bivariate analyses were performed to determine knowledge levels across provider characteristics. Significance was defined as p < 0.05. Results: Of the 231 participants, 45% were medical students, 34% were residents or fellows, 11% were medicine attendings (non-infectious diseases), and 10% were infectious diseases attendings. The overall mean score was 9.79 (out of 25; range = 0–23, p ⩽ 0.001). Mean scores differed significantly ( p < 0.001) across groups, including 7.68 for students (range = 0–16), 10.61 for residents/fellows (range = 3–17), 10.41 for non-infectious diseases attendings (range = 4–18), and 16.38 for infectious diseases attendings (range = 6–23). Familiarity with the reverse sequence algorithm was low with only 22% having heard of it. Infectious diseases attendings were significantly more knowledgeable compared to other groups. Overall and across domains, infectious diseases attendings had significantly higher scores except when compared to non-infectious diseases attendings in the epidemiology domain and residents/fellows in the transmission domain. Conclusion: Overall syphilis knowledge among non-infectious diseases medical providers was low. Improved education and clinical training are needed to promote early diagnosis, treatment, and prevention efforts.